Measures of robustness and stability to scheduling problems with uncertainty: A review of the state of the art - Asmat U., Rafael (2019)
In this work we summarize the different and more used approaches and policies found in the literatura to measure the robustness and stability of solutions for scheduling problems. These policies are based in the analysis of proactive scheduling problems with an approach of planning scenes. Moreover, we present and review the more recent studies developed to measure the robustness and the stability of solutions for uncertainty scheduling problems and we suggest future lines of research.